Children of Immigrants and Nonmarital Fertility in the United States - Anyawie, Maurice (Migration Letters, 2022)
There is vast research on the patterns and consequences of nonmarital fertility; but relatively little is known about how the patterns of nonmarital fertility vary according to the immigrant generational status of young adult Americans. This paper examines differences in the risk of experiencing a nonmarital first birth between children of immigrants and children of native-born Americans. Results from the longitudinal data and event history models show that children of immigrants are less likely to have a nonmarital first birth compared to children of native-born Americans. A range of demographic and mitigating factors drive these nonmarital fertility patterns but do not fully account for the differences. I provide possible explanations for children of immigrants’ lower risks of experiencing a nonmarital first birth. This study provides new insights into differentials into the family context faced by the next generation of Americans.